Epidemiology of pediatric cardiopulmonary resuscitation - Tania Miyuki Shimoda-Sakano (Jornal de Pediatria, 2020)
Objective: To analyze the main epidemiological aspects of prehospital and hospital pediatric cardiopulmonary resuscitation and the impact of scientific evidence on survival. Source of data: This was a narrative review of the literature published at PubMed/MEDLINE until January 2019 including original and review articles, systematic reviews, meta-analyses, annals of congresses, and manual search of selected articles. Synthesis of data: The prehospital and hospital settings have different characteristics and prognoses. Pediatric prehospital cardiopulmonary arrest has a three-fold lower survival rate than cardiopulmonary arrest in the hospital setting, occurring mostly at home and in children under 1 year. Higher survival appears to be associated with age progression, shockable rhythm, emergency medical care, use of automatic external defibrillator, high-quality early life support, telephone dispatcher-assisted cardiopulmonary resuscitation, and is strongly associated with witnessed cardiopulmonary arrest. In the hospital setting, a higher incidence was observed in children under 1 year of age, and mortality increased with age. Higher survival was observed with shorter cardiopulmonary resuscitation duration, occurrence on weekdays and during daytime, initial shockable rhythm, and previous monitoring. Despite the poor prognosis of pediatric cardiopulmonary resuscitation, an increase in survival has been observed in recent years, with good neurological prognosis in the hospital setting. Conclusions: A great progress in the science of pediatric cardiopulmonary resuscitation has been observed, especially in developed countries. The recognition of the epidemiological aspects that influence cardiopulmonary resuscitation survival may direct efforts towards more effective actions; thus, studies in emerging and less favored countries remains a priority regarding the knowledge of local factors. Resumo: Objetivo: Analisar os principais aspectos epidemiológicos da ressuscitação cardiopulmonar pediátrica pré-hospitalar e hospitalar e o impacto das evidências científicas na sobrevida. Fonte de dados: Revisão narrativa da literatura publicada Pubmed/Medline até janeiro de 2019, inclusive artigos originais e de revisão, revisões sistemáticas, metanálises, anais de Congresso, além de busca manual dos artigos selecionados. Síntese dos dados: Os cenários pré-hospitalar e hospitalar apresentam características e prognósticos distintos. A parada cardiorrespiratória pré-hospitalar pediátrica apresenta sobrevida três vezes menor do que a hospitalar, ocorre em sua maioria nas residências e nos menores de um ano. A maior sobrevida parece estar associada a progressão da idade, ritmo chocável, atendimento por serviço médico de emergência, uso de desfibrilador externo automático, suporte básico de vida precoce de alta qualidade e orientação de ressuscitação cardiopulmonar via telefônica por atendente e está fortemente associada com parada cardiorrespiratória presenciada. No cenário hospitalar, observou-se maior incidência em menores de um ano e mortalidade crescente com a idade. Maior sobrevida foi observada quanto menor duração da ressuscitação cardiopulmonar, ocorrência em dias da semana e período diurno, ritmo chocável inicial e monitorização prévia. Apesar do prognóstico reservado da ressuscitação cardiopulmonar pediátrica, observou-se nos últimos anos incremento da sobrevida com bom prognóstico neurológico no cenário hospitalar. Conclusões: Houve grande avanço na ciência da ressuscitação cardiopulmonar pediátrica, especialmente em países desenvolvidos. O reconhecimento dos aspectos epidemiológicos que influenciam a sobrevida da ressuscitação cardiopulmonar pode direcionar esforços para ações mais efetivas. Assim, a pesquisa em países emergentes e menos favorecidos persiste como prioridade no conhecimento de fatores locais.